Effect of PACAP/PAC1R on Follicle Development of Djungarian Hamster (Phodopus sungorus) with the Variation of Ambient Temperatures - Yan Qi; Huiliang Xue; Jinhui Xu; Ming Wu; Lei Chen; Laixiang Xu (Biology, 2023)
In Phodopus sungorus, the relationship between pituitary adenylate cyclase-activating polypeptide (PACAP) and its receptor (PAC1R), follicle-stimulating hormone (FSH), and follicle development remains unclear. In this study, we found that the development of growing follicles and antral follicles were inhibited at low (8 °C, 14 °C) and high (29 °C) temperatures. Meanwhile, PACAP/PAC1R expression and follicle-stimulating hormone (FSH) serum concentration significantly decreased during ambient temperatures of 8 °C, 14 °C and 29 °C compared to 21 °C. Thus, ambient temperature may influence the expression of PACAP/PAC1R and the synthesis of FSH for involvement in follicle development. Moreover, PACAP/PAC1R had major functional elements including PKA/PKG and PKC phosphorylation sites, which may involve in the pathway of FSH synthesis through cAMP-PKA and its downstream signal pathway. Moreover, there was a significant positive correlation between the expression levels of PACAP/PAC1R and the number of the growing and antral follicles, as well as the serum FSH concentration and the number of antral follicles. However, there was no significant correlation between the expression levels of PACAP/PAC1R and the serum FSH concentration, indicating a complicated pathway between PACAP/PAC1R and FSH. In conclusion, ambient temperature affects the expression of PACAP/PAC1R and the serum FSH concentration. The expression of PACAP/PAC1R and the serum FSH concentration are correlated with follicle development, which implies that they are involved in follicle development, which will ultimately influence the reproduction of Phodopus sungorus. This study can lay the foundation for future investigation on the regulation mechanism of reproduction in Phodopus sungorus.